Genomic Analysis of Prophages Recovered from Listeria monocytogenes Lysogens Found in Seafood and Seafood-Related Environment - Hue Thi Kim Vu; Matthew J. Stasiewicz; Soottawat Benjakul; Kitiya Vongkamjan (Microorganisms, 2021)
A prophage is a phage-related sequence that is integrated into a bacterial chromosome. Prophages play an important role in bacterial evolution, survival, and persistence. To understand the impact of Listeria prophages on their host genome organizations, this work sequenced two L. monocytogenes strains (134LM and 036LM), previously identified as lysogens by mitomycin C induction. Draft genomes were generated with assembly sizes of 2,953,877 bp and 3,000,399 bp. One intact prophage (39,532 bp) was inserted into the comK gene of the 134LM genome. Two intact prophages (48,684 bp and 39,488 bp) were inserted in tRNA-Lys and elongation-factor genes of the 036LM genome. The findings confirmed the presence of three corresponding induced phages previously obtained by mitomycin C induction. Comparative genomic analysis of three prophages obtained in the newly sequenced lysogens with 61 prophages found in L. monocytogenes genomes, available in public databases, identified six major clusters using whole genome-based phylogenetic analysis. The results of the comparative genomic analysis of the prophage sequences provides knowledge about the diversity of Listeria prophages and their distribution among Listeria genomes in diverse environments, including different sources or geographical regions. In addition, the prophage sequences and their insertion sites contribute to the genomic diversity of L. monocytogenes genomes. These data of prophage sequences, prophage insertion sites, and prophage sequence comparisons, together with ANIb confirmation, could be useful for L. monocytogenes classification by prophages. One potential development could be refinement of prophage typing tools for monitoring or surveillance of L. monocytogenes contamination and transmission.